Healthcare: Public Policies, Social Practices, and Individual Experiences. An Introduction - Mircheva Gergana; Popova Olga (Comparative Southeast European Studies)
This thematic section focuses on health as a multilayered political, economic, and cultural phenomenon. Based on case studies from Southeastern Europe, the four articles in the section pose research questions that are important for understanding the interplay between personal experiences of using healthcare services, trust in the healthcare system, and the governance of healthcare service provision in the region. The articles build on complementary perspectives on individual experiences of interacting with healthcare providers, social issues, and public health strategies, drawing a multidimensional “health map” with interrelated but sometimes diverging arguments. This allows a better understanding of the issues of health and illness in turbulent times of social crises and provides a conceptual basis for healthcare policies in Southeastern Europe.